The Effect of Bocce Games on the Physical Fitness of Children with Grahita SLB AL-GIFARI During the Covid-19 Pandemic - Firdaus, Firdaus; Irfan, Irfan (Journal of Physical and Outdoor Education, 2023)
In this research, the problem is mentally retarded children do not have goog physical fitness. So it is necessary to find a bocce game model to measure children’s physical fitness this study aims to measure the effect of playing bocce on the physical fitness of mentally retarded children in the Al-Gifari SLB School Bima City. This research method is quasi-experimental. Research design using One Group Prestes-Posttest Design. The research population is mentally retarded children age 13-15 years at the Al-Gifari SLB School, Bima City.  The research sampel is 6 male students and 4 famale students. The test uses the Indonesia physical fitness test (normal TKJI), for ages 13-15 using the 100 meter run test, hanging your elbows, flying, down for 30 second, jumping strainght up. And running 30 meters. The purpose of the test is to measure students’physical fitness. The data analysis technique uses the t test thtough thr normality requirements test. The results showerd that there was an effect of playing bocce on fitness. The results of data analysis to answer the proposed research hypothesis obtained a t-count value of 6.573 with a significant 0.05% with d.f= 8 and a null hypothesis in the t-value table of 2.306. thus, the null hypothesis is rejected and the alternative” there is an effect of playing bocce on the level of physical fitness of mentally retarded children at SLB Al-Gifari Bima City” Accepted